Integrating Unani medicine in managing major depressive disorder: a series of case reports - Meraj, Meraj; Khan, Noushiba; Ishaquddin, Abdul Rehman; Khan, Naseem A.; Husain, Sadique; Virpara, Prachi; Kamal, Shaikh A. N.; Sameer, Mohammad (International Journal Of Community Medicine And Public Health, 2025)
Major depressive disorder (MDD) is a chronic condition affecting mood, cognition, and physical well-being. In Unani medicine, MDD is similar to Mālankhūliyā. This case series aimed to integrate Unani medicine into an outpatient model for holistic MDD treatment. Seven participants (four females, three males) with moderate to severe MDD were diagnosed using the DSM-V and Unani criteria for Mālankhūliyā Sawdāwī. They underwent a 19-week treatment protocol, consisting of 17 weeks of active treatment and 2 weeks of observation. The Unani-based approach combined Ilāj bi’l Tadbīr (regimenal therapy) like Naṭūl (forehead irrigation with medicated oil), Sa‘ūṭ (nasal drops), and Tadhīn (oiling). Pharmacotherapy included Majoon Njah, Jawarish Shahi (5 g twice daily), and Dawa-ul-Misk Sada with Arq Gawzaban (5 g and 60 ml twice daily). Conventional antidepressants were tapered and discontinued. Outcomes were assessed using primary self-reported questionnaires and secondary measures including quality of life (QoL) and routine blood tests. The intervention showed significant reductions in the Hamilton depression rating scale (HDRS-21) (p<0.001), Beck depression inventory (BDI) (p<0.002), and insomnia, measured by the insomnia severity index (ISI) (p<0.004). QoL improved significantly (p<0.007). Thus, the integrative Unani medicine approach demonstrated efficacy in managing MDD. The combination of pharmacotherapy and regimenal therapy significantly alleviated depressive symptoms and improved QoL. However, further rigorous studies are needed to confirm its broader applicability in MDD treatment.